Huizinga on America. (August 2015) - Torpey, John
The Dutch historian Johan Huizinga, perhaps best known for his writings on the Middle Ages and on play in human life, also wrote rather extensively on the United States. He both followed and, in certain respects, sharply criticized Alexis de Tocqueville's views on America, while ultimately echoing many of Max Weber's views of the United States and more generally of the rationalization of modern life. Given that Huizinga is known primarily for his writings about culture, it is intriguing that his perspective on America was heavily skewed toward an emphasis on the economic aspects of American life. Huizinga's writings on America offer an intriguing Dutch perspective that has been widely missed in social scientific discussions of the United States and on the notion of American exceptionalism.